Synthesis and Characterization of New Thiolated Chitosan Nanoparticles Obtained by Ionic Gelation Method. (15th December 2015) - Esquivel, Reynaldo; Juárez, Josué; Almada, Mario; Ibarra, Jaime; Valdez, Miguel A.
Abstract : We derivatized low molecular weight chitosan (LMWC) with 3-mercaptopropanoic acid (3-MPA) by a coupling reaction. The chemical modification of LMWC was characterized by Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance, 1 HNMR. We researched the influence of 3-MPA on the nanoparticles formation by ionic gelation method using sodium tripolyphosphate (TPP) as cross-linker reagent. In order to optimize the nanoparticles formation, we studied the effect of the pH solution and molar ratio on nanoparticles stability. Analyses of particle size, morphology, and surface charge were determined by dynamic light scattering, Atomic Force Microscopy, and zeta potential, respectively. It was found that formation of semispherical and stable nanoparticles was improved due to the chemical modification of chitosan. Optimized semispherical nanoparticles of thiolated chitosan were synthesized with the parameters (pH 4.7, molar ratios 1 : 106). Additionally, we reported the thermodynamic profile of the nanoparticles formation determined by isothermal titration calorimetry (ITC). The aggregation process achieved to form nanoparticles of thiolated and nonmodified chitosan consisted of two stages, considering one binding site model. Gibbs free energy( Δ G ) and binding constant (K a ) describe the aggregation process of thiolated chitosan/TPP, which is an initial reaction and followed by an endothermic stage. These results are promising for the possible application of these nanoparticles as nanocarriers and delivery systems.